The Dragon on the Path and the Emerald of Love: A Nietzschean reading of Rūmī’s concept of love - Arani Hamidreza Mahboobi (Open Theology, 2022)
Facing suffering and death, or what is known as human fragility, does not seem all that difficult and challenging in the presence of a morally responsible God or the primordial source of all existence. However, if our theodicy does not allow for the existence of such a God or primordial source, as in Ashʿarite theology or Schopenhauer’s philosophy, then the encounter with human fragility necessitates a more sophisticated explanation. Schopenhauer, by rejecting the loving Christian God, adopts the Buddhist solution to death which, he claims, has been maintained in Sufism. While recognizing Schopenhauer’s metaphysics, Nietzsche disagrees with his moral approach and attempts to address human vulnerability from an aesthetic standpoint. In this article, I argue that Rūmī, following Ashʿarite theodicy, attempts to transcend the moral position of theologians with his concept of love and, instead of appealing to the dominant asceticism of fear and terror, confronts human fragility through the framework of his mysticism of love. The article then makes an effort to provide a reasonable interpretation of this mysticism in light of Nietzsche’s aesthetic metaphysics.